The Italian Rare Pancreatic Exocrine Cancer Initiative. Issue 4 (August 2019) - Brunetti, Oronzo; Luchini, Claudio; Argentiero, Antonella; Tommasi, Stefania; Mangia, Anita; Aprile, Giuseppe; Marchetti, Paolo; Vasile, Enrico; Casadei Gardini, Andrea; Scartozzi, Mario; Barni, Sandro; Delfanti, Sara; et al.
Introduction: Exocrine pancreatic cancers include common type pancreatic ductal adenocarcinoma and cystic neoplasms, which account for 85% and 10% of cases, respectively. The remaining 5% are rare histotypes, comprising adenosquamous carcinoma, acinar cell carcinoma, signet ring cell carcinoma, medullary carcinoma, pancreatoblastoma, hepatoid carcinoma, undifferentiated carcinoma and its variant with osteoclast-like giant cells, solid pseudopapillary carcinoma, and carcinosarcoma. Due to their low incidence, little knowledge is available on their clinical and molecular features as well as on treatment choices. The national initiative presented here aims at the molecular characterization of series of rare histotypes for which therapeutic and follow-up data are available. Methods: A nationwide Italian Rare Pancreatic Cancer (IRaPaCa) task force whose first initiative is a multicentric retrospective study involving 21 Italian cancer centers to retrieve histologic material and clinical and treatment data of at least 100 patients with rare exocrine pancreatic cancers has been created. After histologic revision by a panel of expert pathologists, DNA and RNA from paraffin tissues will be investigated by next-generation sequencing using molecular pathway–oriented and immune-oriented mutational and expression profiling panels constructed availing of the information from the International Cancer Genome Consortium. Bioinformatic analysis of data will drive validation studies by immunohistochemistry and in situ hybridization, as well as nanostring assays. Conclusions: We expect to gather novel data on rare pancreatic cancer types that will be useful to inform the design of therapeutic choices.